INCREASE OF RESISTIBILITY OF DEFORMING ACCESSORY, CUTTING INSTRUMENT, DETAILS OF EQUIPMENT AND MACHINES IN THE RESULT OF BOROSILICATING AND BOROCARRBONITRIDING IN POWDER MIXTURES COATINGS WITHOUT USING OF SPECIAL EQUIPMENT - M. V. Sitkevich (Литьë и металлургия)
The results of investigations of the structure and characteristics of the surface coatings of structural and tool steels, subjected to borosilicating at temperatures 900-950°C and low-temperature НТО (450-550°C) in the system carbon-nitrogen-boron in powder mixtures and coverings without special equipment, are considered. The data on production testings of different types of details, which prove that due to diffuse hardening the increase of resistance in 2-10 times is provided depending on types of details and conditions of their working, are presented.